THE EFFECT OF COGNITIVE BEHAVIORAL THERAPY (CBT) ON TIME MANAGEMENT AND WORK HABITS AMONG ADOLESCENTS WITH ADHD - Moshe, Varda (E-Journal VFU, 2025)
This article presents a comprehensive literature review and meta-analytic synthesis of recent empirical studies examining the effectiveness of Cognitive Behavioral Therapy (CBT) in improving time management and study habits among adolescents diagnosed with Attention-Deficit/Hyperactivity Disorder (ADHD). The aim is to identify consistent patterns, treatment moderators, and practical implications for clinical and educational contexts.